Pressures on plagiarism: a case study in UiTM Sabah / Mohd Faizal Louis and Mohd Roze Abdullah - Louis, Mohd Faizal; Abdullah, Mohd Roze (2017)
Plagiarism is an intentional action of using others ideas and words without clear acknowledgement on the source of information that has been taken. The information taken by the student are normally from the internet sources such as Wikipedia, blogs and article in which are being misuse by student whereby they exploit the ideas and words of the authors without recognizing and giving credit to the original author. Plagiarism also perceived as a form of intellectual dishonesty that involve unintentionally taking someone else's work without properly acknowledging where the ideas came from or intentionally copying someone else's work and passing it off as your own (Palmquist, 2003). Plagiarism is a serious problem among student nowadays as the rapid technology developments make it easier for student to get information from the internet. The growth of technology in this modern era revolve the students tend to plagiarize since the widespread availability of World Wide Web pages in this internet age causing plagiarism become rampant in the Universities and colleges level.